Problems participation of the lawyer defender in proof on criminal trial (Journal of actual problems of jurisprudence, 2019)
In this article the author considers the problem of representation by counsel - defense counsel in proving criminal cases,including those discussed activities of the submission and the gathering of evidence, and the opportunity to changethe rules of modern legislation. This article discusses the theoretical issues and activities of defense counsel involvedin the gathering of evidence. To resolve the criminal case , to prove legally guilt or innocence of the person againstwhom the criminal case . In this regard, the literature is justifi ed write that proof - this is the basic element , the coreof the criminal process. In science, the criminal proceedings are discussions about the possibility of the participationof defense counsel in proving a criminal case. Thus , despite the legal right to participate in the gathering of thedefense evidence , the lack of a mechanism for its implementation does not allow to fully implement the constitutionalprinciples such as competition and the defendant's right to a defense.Key words: lawyer, defender, proofs, criminal trial, participants.